Relationship between Humor Style and Psychological Well-Being of Bangladeshi University Students (Bangladesh Journal of Psychology, 2024)
Humor style plays an important role in maintaining psychological well-being. However, no research has yet addressed these concerns. Thus, this study aimed to determine the humor styles and psychological well-being of Bangladeshi university students and the relationship between humor style and their psychological well-being. A sample of 502 university students (346 males and 156 females) was conveniently selected for data collection. The average age of the students was 22.77±1.95 years. The Banglaversion of the Humor Styles Questionnaire and Warwick-Edinburgh Mental Well-being Scale were utilized to gather relevant data. The results revealed that positive humor styles, specifically Affiliative (36.75±8.71) and Self-Enhancing (36.39±8.74), were dominant among Bangladeshi university students than negative humor styles. Male students exhibited a higher tendency towards negative humor styles, such as aggressive humor (25.55±7.13) and self-defeating humor (28.05±8.49), compared to their female counterparts. Additionally, urban students demonstrated a higher inclination towards affiliative humor styles (37.51±8.87) in comparison to rural students. Furthermore, it was found that Bangladeshi male university students had higher levels of psychological well-being compared to female students. A total of 15.9% reported poor psychological well-being. Psychological well-being is positively related to self-enhancing and affiliative humor but negatively related to aggressive humor. In conclusion, student’s dominant humor style is positive humor style and the majority of students have moderate psychological well-being; however, a significant number of students, particularly females, have poor psychological well-being. Understanding the findings can help to design interventions that promote mental health among Bangladeshi university students.Bangladesh Journal of Psychology Vol. 24, December 2024, pp. 33-48